Socio-economic context of education in the light of selected indicators - Rafał Piwowarski (Studia z Teorii Wychowania)
This text draws some socio-economic problems of education, illustrated with selected indicators. Apart introduction, which presents components of HDI, the paper is devided – into two main parts. The first one deals with expenditure on education, in the context of student achievements and social development. The second part reflects new education contexts such as COVID-19, inclusive education and desired changes in the structure of education.